2000
DOI: 10.4049/jimmunol.164.12.6406
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 and the Dangers of Immune Polarization: Excessive Type 1 and Type 2 Cytokine Responses Induce Distinct Forms of Lethal Immunopathology in Murine Schistosomiasis

Abstract: To dissect the controversial roles of type 1 and type 2 cytokines to the pathogenesis of schistosomiasis, we generated IL-10/IL-4- and IL-10/IL-12-deficient mice that develop highly polarized type 1 and type 2 cytokine responses, respectively. Interestingly, the Th1-polarized IL-10/IL-4-deficient mice rapidly lost weight at the onset of egg-laying and displayed 100% mortality by wk 9 postinfection. This acute mortality was linked to overexpression of the proinflammatory mediators IFN-γ, TNF-α, and inducible NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
376
2
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(414 citation statements)
references
References 48 publications
31
376
2
5
Order By: Relevance
“…In confirmation, schistosome-infected IFN-c receptor-deficient and IFNc-deficient mice displayed, and the administration of anti-IFN-c antibody to infected mice resulted in, increased fibrosis and diminished granuloma size and cellularity [26][27][28][29]. In addition, exogenous application of IFN-c has been shown to reduce collagen levels [30], and increased secretion of IFN-c has anti-fibrotic actions [31]. These observations strikingly correlate with our results and leave little doubt that the reduction in Th1 responses (signified by the absence of IFN-c) was responsible for the changes in liver pathology as displayed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In confirmation, schistosome-infected IFN-c receptor-deficient and IFNc-deficient mice displayed, and the administration of anti-IFN-c antibody to infected mice resulted in, increased fibrosis and diminished granuloma size and cellularity [26][27][28][29]. In addition, exogenous application of IFN-c has been shown to reduce collagen levels [30], and increased secretion of IFN-c has anti-fibrotic actions [31]. These observations strikingly correlate with our results and leave little doubt that the reduction in Th1 responses (signified by the absence of IFN-c) was responsible for the changes in liver pathology as displayed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a counter-regulatory response to increased levels of pro-inflammatory cytokines. Although a previous study has shown that IL-10 plays a central regulatory role in the pathogenesis of schistosomiasis (Hoffman et al 2000), its relationship to the nutritional status has not been studied (Coutinho et al 2005).…”
Section: Immune Response In Undernourished Mice Infected With S Mansonimentioning
confidence: 99%
“…Hoffmann and colleagues clearly demonstrated that in schistosome-infected mice, IL-10 significantly suppressed type 1 and type 2 cytokines' development in IL-4 --and IL-12 --deficient mice, respectively, and thereby impeded the development of severe egg-induced pathology in the single cytokine-deficient animals. 33 To further define the contribution of IL-10 in persistent infections, Hesse generated the IL-10/recombination-activating gene (RAG)2 -deficient mice and demonstrated that innate effectors and regulatory T…”
Section: Hiv Vaccination Decreases Expression Of Sea-induced Il-13mentioning
confidence: 99%